2017
DOI: 10.1159/000473702
|View full text |Cite
|
Sign up to set email alerts
|

The Inhibitory Effect of Eplerenone on Cell Proliferation in the Contralateral Kidneys of Rats with Unilateral Ureteral Obstruction

Abstract: Background: The unilateral ureteral obstruction (UUO) model not only induces renal interstitial fibrosis in the obstructed kidney but also induces injury in the contralateral kidney. We hypothesized that activation of the mineralocorticoid receptor (MR) may induce fibrosis in the early stage of UUO. Methods: Thirty male Sprague-Dawley rats weighting 200 ± 10 g were used in this study and randomly divided into 3 groups: a UUO group, a UUO and eplerenone group, and a sham group. The contralateral kidney and plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 25 publications
4
21
0
Order By: Relevance
“…Renal failure induced by obstructive nephropathy is related to contralateral kidney injury [5]. In this study, we first confirmed cell pyroptosis in the contralateral kidney in UUO rats, which was induced by MR activation.…”
Section: Discussionsupporting
confidence: 68%
See 4 more Smart Citations
“…Renal failure induced by obstructive nephropathy is related to contralateral kidney injury [5]. In this study, we first confirmed cell pyroptosis in the contralateral kidney in UUO rats, which was induced by MR activation.…”
Section: Discussionsupporting
confidence: 68%
“…Our previous study has already indicated that plasma Ald concentrations were elevated in the UUO animals [5]. To confirm this in the current study and further investigated whether MR activation results in inflammatory activation of NLRP3 inflammasome, we examined the expression of serum and glucocorticoid-inducible protein kinase-1 (SGK-1) and nuclear factor kappa B (NF-κB) using western blot.…”
Section: The Expression Of Serum and Glucocorticoidinducible Protein supporting
confidence: 74%
See 3 more Smart Citations